2023
DOI: 10.9734/ijpss/2023/v35i92903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weeding Regime and Row Direction on Growth and Yield of Upland Rice in Uganda

Abstract: A study determined the effects of row direction and integrated weed management on the growth, productivity and economics of upland rice at Ikulwe Research Station using a completely randomized block design, replicated thrice with NAMCHE 5 upland rice in Uganda (2021b & 2022b). 12 treatments with 6 weeding regimes namely Pre- emergence Butanil (PREB) + 1hand hoeing (HH), 2HH, 3HH, PREB + Post emergence Butanil (POEB), weekly weeding (42 days) and control (EW & NS orientation) were adopted. Nitrogen (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Rice, beans, soybeans and groundnuts being C 3 plants are not efficient in utilizing Cabondioxide like C 4 crops. Kaiira et al (2023) recorded higher rice growth and grain yields in the East-West row orientation. Borger (2020) reported that East-west crops more effectively shade weeds in the inter-row space than NS row crops.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Rice, beans, soybeans and groundnuts being C 3 plants are not efficient in utilizing Cabondioxide like C 4 crops. Kaiira et al (2023) recorded higher rice growth and grain yields in the East-West row orientation. Borger (2020) reported that East-west crops more effectively shade weeds in the inter-row space than NS row crops.…”
Section: Introductionmentioning
confidence: 91%
“…This may be related to more efficient absorption of solar radiation under competition between rice and the phenotypically tall soybean crop planted in the East-West row direction. Kaiira et al (2023) reported that rice being a C 3 plant produced higher rice growth and grain yields in the EW row direction due to reduced weeds, more efficient in utilizing Cabondioxide and solar radiation. Similar observations were earlier made by Borger (2020).…”
Section: Plant Height Tiller and Panicles For Rice During 2022 And 2023mentioning
confidence: 99%
See 1 more Smart Citation